Development of surface coating materials of wax esters and epoxides for coating industries - Abd Ghani, Norani (2012)
There has been an increasing interest and strong demand for fine quality coating materials that can be applied to various substrates. Coating materials contained high proportion of acrylate based products which affect human health related toxicity, primarily on carcinogenicity. Researchers make efforts to eliminate this substrate by replacing with other materials such as wax esters and epoxides from renewable raw materials especially oil crops. A major problem with this kind of application is, coating characteristics features are very low, thus ingredient of coating formulation was developed to improve coating characteristics.